Dominant Body Types And Their Effect On Sensory Preferences (Audio – Visual – Motor) and Some Physical And Motor Abilities in Secondary School Students - Saed, Qais (Journal of Physical Education, 2016)
Body types directly affect individuals because it can be a major source of confidence. Body types can affect the individual negatively and force him to isolation. The importance of the study lies in identifying prominent body types according to Sheldon theory of Body Types (extreme ectomorphic – extreme endomorphic) as well as identifying their motor and physical abilities. The researcher aims at developing these motor and physical abilities and finding the best methods of teaching that suits them. The subjects high school students from Al Qadisia governorate all ranged either extreme ectomorpic or extreme endomorph. The experiment was conducted on 166 students (98 ectomorphic students representing 95% of the subjects and 68 endomorphic representing 41% of the subject. The researcher used SPSS as well as many statistical operations to come up with the results. The results showed that extreme ectomorphic developed better than extreme endomorphic students.